Parkour, deviance and leisure in the late-capitalist city : an ethnography - Raymen, Thomas (Bingley, U.K. : Emerald Publishing Limited, 2018)
Taking us on an ethnographic journey into the spatially transgressive practice of parkour and freerunning, Parkour, Deviance and Leisure in the Late-Capitalist City: An Ethnography attempts to explain and untangle some of the contradictions that surround this popular lifestyle sport and its exclusion from our hyper-regulated cities. While the existing criminological wisdom suggests that these practices are a form of politicised resistance, this book positions parkour and freerunning as hyper-conformist to the underlying values of consumer capitalism and explains how late-capitalism has created a contradiction for itself in which it must stoke desire for these lifestyle practices whilst also excluding their free practice from central urban spaces. Drawing on the emergent deviant leisure perspective, this book takes us into the life-worlds of young people who are attempting to navigate the challenges and anxieties of early adulthood. For the young people in this study, consumer capitalism's commodification of rebellious iconography offered unique identities of 'cool individualism' and opportunities for flexibilised employment; while the post-industrial 'creative city' attempted to harness parkour's practice, prohibitively if necessary, into approved spatial contexts under the buzzwords of 'culture' and 'creativity'. This book offers a vital contribution to the criminological literature on spatial transgression, and in doing so, engages in a critical reappraisal of the evolution of the relationships between work, leisure, identity and urban space in consumer capitalism.
Prelims -- Chapter 1: The 'paradox' of Parkour -- Chapter 2: Moving with the times: parkour, leisure and social change -- Chapter 3: Ultra-realism, parkour and capitalist ideology -- Chapter 4: Movers and shakers -- Chapter 5: Zombie cities -- Chapter 6: The parkour city -- Chapter 7: 'Sorry lads (but I've got to move you on)' -- Chapter 8: Conclusion and futures -- References -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Parkour; Sports & Recreation -- Sociology of Sports; Sociology: sport & leisure